Chemical Composition and Antioxidant Activities of Five Samples of Prunus mume Umezu from Different Factories in South and East China - Zhi-Yi Chen; Yao-Sheng Lin; Xue-Ming Liu; Jing-Rong Cheng; Chun-Ying Yang (Journal of Food Quality)
This paper investigated chemical composition and antioxidant activities of umezu, pickling liquid of Prunus mume, from different factories in South and East China. The organic acid and phenolic acid profiles were also analyzed. Results showed that umezu was rich in organic acids and extremely sour as P. mume fruit in addition to its high NaCl level (≥20%). Total acid in umezu was more than 43.78 g/L in which main organic acids were citric acid and malic acid. Umezu contained more than 250.54 mg GAE/L total phenolic in which dominant phenolic acids were hydroxycinnamic acid derivatives. Umezu exhibited powerful antioxidant activities in ORAC, ABTS, DPPH, and FRAP assays. Reducing sugar, phenolic compounds, and antioxidant activities of umezu were affected by sample origins and fruit cultivars. Given its rich flavor components and high antioxidant activity, umezu could serve as a new dietary supplement or a natural preservative in food industry.